Analisis Pengembangan Skula Kompos Berbasis Kegiatan Pemberdyaan Masyarakat (Studi Kasus : PT. Solusi Bangun Indonesia Tbk Pabrik Cilacap) - Prasadi, Oto; Prastya, Andika; Fauzi, Muhammad; Nurochman, Budi (Edumedia Solution, 2023)
The compost school (skula kompos) is a product of community empowerment activities that focuses on developing education on household-based organic waste management. This program is one of a series of innovations in the Baruwani Program (Bala Runtah Watu Geni) which was initiated in 2019 by PT Solusi Bangun Indonesia Tbk, Cilacap factory. The baruwani program itself focuses on waste sorting and processing activities in the community where the output produced not only reduces waste generation, but produces other innovations, especially to support the successful use of waste as an alternative fuel to replace coal in the cement production process. The benefit of making this compost is to help people optimize the use of household waste so that it can have high use value and be useful as compost fertilizer which in the next stage can be used to support urban farming activities. Making compost and being able to reduce dependence on the use of inorganic fertilizers which contain many compounds that are less environmentally friendly, has the potential to become a social business that has an economic impact. Skula kompos is a forum for outreach and training which is attended by baruwani's assisted communities and other parties who are interested in making compost using the unique method of Skula kompos BSM Subur.